Vaccine Safety: Myths and Misinformation - Geoghegan, Sarah; O’Callaghan, Kevin P.; Offit, Paul A. (Frontiers in Microbiology, 2020)
The World Health Organization has named vaccine hesitancy as one of the top ten threats to global health in 2019. The reasons why people choose not to vaccinate are complex, but lack of confidence in vaccine safety, driven by concerns about adverse events, has been identified as one of the key factors. Healthcare workers, especially those in primary care, remain key influencers on vaccine decisions. It is important, therefore, that they be supported by having easy access to trusted, evidence-based information on vaccines. Although parents and patients have a number of concerns about vaccine safety, among the most common are fears that adjuvants like aluminium, preservatives like mercury, inactivating agents like formaldehyde, manufacturing residuals like human or animal DNA fragments, and simply the sheer number of vaccines might be overwhelming, weakening or perturbing the immune system. As a consequence, some fear that vaccines are causing autism, diabetes, developmental delays, hyperactivity, and attention-deficit disorders, amongst others. In this review we will address several of these topics and highlight the robust body of scientific evidence that refutes common concerns about vaccine safety.